2009
DOI: 10.1159/000235892
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Amyloidosis in Familial Mediterranean Fever with Colchicine: A Case-Control Study in Armenia

Abstract: Objective: To determine whether or not the use of colchicine decreases the risk of amyloidosis among Armenian patients with familial Mediterranean fever (FMF). Subjects and Methods: The study included 99 Armenian patients from the Center of Medical Genetics database with genetically ascertained FMF; 33 had renal amyloidosis and 66 were randomly selected control patients without renal amyloidosis. Self- reported colchicine use was assessed by interviewer-based questionnaire. Results: The patients with incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…On suitable genetic background, inappropriately activated innate immune system cells are supposed to cause unprovoked short-lived bursts of systemic inflammation that gives to the rise clinical presentation of FMF ( 5 ). The most feared long term complication is development of amyloidosis that occurs mostly in untreated patients owing to late diagnosis of disease ( 3 6 ). Despite colchicine treatment, some patients still develop complications of disease due to unapparent chronic subclinical inflammation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…On suitable genetic background, inappropriately activated innate immune system cells are supposed to cause unprovoked short-lived bursts of systemic inflammation that gives to the rise clinical presentation of FMF ( 5 ). The most feared long term complication is development of amyloidosis that occurs mostly in untreated patients owing to late diagnosis of disease ( 3 6 ). Despite colchicine treatment, some patients still develop complications of disease due to unapparent chronic subclinical inflammation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of amyloid A protein (AA) occurs in secondary amyloidosis associated with FMF. Colchicine treatment prevents and retards episodes as well as renal failure when it is initiated early after FMF diagnosis and used regularly (5). In a multicenter study by the Turkish FMF Working Group conducted on 2838 cases, it was reported that the mean age at onset of FMF was 9 years and the mean age at diagnosis was 16 years (6 amyloidosis that might cause chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is recommended that colchicine should be given even in non or partial responders in FMF patients with AA amyloidosis. [12][13][14][15] Proteinuria of more than 0.5 g/24 hours is suggestive of amyloidosis. Nonresponders of colchicine can be treated with anakinra, IL-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%